Application of a topographic pedosequence in the Villány Hills for terroir characterization - Czigány, Szabolcs; Novák, Tibor József; Pirkhoffer, Ervin; Nagy, Gábor; Lóczy, Dénes; Dezső, József; Fábián, Szabolcs Ákos; Świtoniak, Marcin; Charzyński, Przemyslaw (Hungarian Geographical Bulletin, 2020)
Terroir refers to the geographical origin of wines. The landscape factors (topography, parent rock, soil, microbial life, climate, natural vegetation) are coupled with cultural factors (cultivation history and technology, cultivars and rootstock) and all together define a terroir. The physical factors can be well visualized by a slope profile developed into a pedosequence showing the regular configuration of the relevant physical factors for a wine district. In the present study the generalized topographic pedosequence (or catena) and GIS spatial model of the Villány Hills, a historical wine producing region, serves for the spatial representation and characterization of terroir types. A survey of properties of Cabernet Franc grape juice allowed the comparison of 10 vineyards in the Villány Wine District, Southwest Hungary. Five grape juice properties (FAN, NH3, YAN, density and glucose + fructose content) have been found to have a moderate linear relationship (0.5 < r2 < 0.7) with the Huglin Index (HI) and aspect. Aspect, when determined on the basis of angular distance from South (180°), showed a strong correlation (r2 > 0.7) with FAN, NH3, YAN, sugar and density and moderate correlation with primary amino nitrogen (PAN). HI showed a correlation with three nitrogen related parameters FAN, NH3, YAN, density and glucose + fructose content. Elevation and slope, however, did not correlate with any of the chemical properties.